Consider the $1+1$ wave equation $$ u_{tt} -c^2 u_{xx} = 0 $$

The following page from my lecture notes explains d'Alembert's solution to this


As you can see, they have used the substitution $$ \xi = x + ct \hspace{5 mm} \eta = x - ct $$

I understand how they have deduced that $u_x = u_\xi + u_\eta$. However, I'm unsure of how they obtained their result for $u_{xx}$.

I would have worked this out using the chain rule, as follows $$ u_{xx} = \frac{\partial}{\partial \xi} \left( u_\xi + u_\eta \right) \cdot \frac{\partial \xi}{\partial x} + \frac{\partial}{\partial \eta} \left( u_\xi + u_\eta \right) \cdot \frac{\partial \eta}{\partial x} = u_{\xi \xi} + u_{\eta \xi} + u_{\xi \eta} + u_{\eta \eta} $$ This is only equal to their derived result for $u_{xx}$ if we assume that $u_{\eta \xi} = u_{\xi \eta}$. This leads me on to my first question: (why) can we say that $u_{\eta \xi} = u_{\xi \eta}$?

Secnd question: further down in these notes, it says that the boundary condition $u_t(x,t) = \psi (x)$ tells us that $$ f'(x) - g'(x) = \frac{1}{c} \psi(x) $$

How was this result obtained? I cannot see how they have deduced this?


$u_{\xi\eta}$=$u_{\eta\xi}$ because the order of differentiation does not matter if the function is $C^2$, more information here.

And if we have



$$u_t=\frac{\partial u}{\partial \xi}\frac{\partial \xi}{\partial t}+\frac{\partial u}{\partial \eta}\frac{\partial \eta}{\partial t}=cf'(\xi)-cg'(\eta)$$ because $\frac{\partial \xi}{\partial t}=c$ and $\frac{\partial \eta}{\partial t}=-c.$




Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.